Study of adverse events following 2018 sub-national yellow fever vaccination in Ghana - Douglas Adu-Fokuo; Feng Cheng; Emily Yin; Elizabeth Giwa (Journal of Vaccines and Immunology - Peertechz Publications, 2023)
Background: According to the Centers for Disease Control and Prevention (CDC), globally there is an estimated 200,000 cases of Yellow Fever Virus yearly, causing 30,000 deaths annually, with 90% of cases occurring in Africa. Where about 20% to 50% of people who get infected and develop severe symptoms from the yellow fever virus die.  WHO report showed that Ghana was among 27 African countries with a high risk of yellow fever outbreak at any time. In response, there was a need to amplify the immunization campaign against yellow fever. Ghana in collaboration with WHO, GAVI, the Vaccine Alliance, and UNICEF began a sub-national campaign to vaccinate approximately 5.3 million people against yellow fever targeting people between ages 10 and 60 years from November 28 to December 4, 2018. 459 Adverse Events Following the Immunization (AEFI) in Ghana were reported from 28th November 2018 to 1st January 2019. The yellow fever vaccine is regarded as one of the safest, but with few adverse events. Therefore, there is a need to assess the severity of the reported adverse events following immunization in the 2018 sub-national yellow fever immunization program in Ghana. Objective: To study the Seriousness of adverse events following yellow fever vaccination in Ghana. Methodology: A retrospective review of AEFI data through a surveillance system during a Yellow Fever vaccination campaign in Ghana. The data comprised suspected 459 adverse events following the immunization (AEFI). The reported AEFI from 28th November 2018 to 1st January 2019 was used for this study as secondary data. A total of 5.3 million people were vaccinated. All vaccine recipients were between the ages of 10 years to 60 years. Data were analyzed using frequencies and descriptive statistics in STATA version 15. Findings and discussions: The study showed 459 (0.00086%) per 5.3 million recipients reported adverse events. The AEFI occurred mostly among females and persons aged 30-39 years. Out of the 459 recipients with adverse events, 432 (99.3%) recovered, and 3 (0.7%) died. The most common adverse event per region, sex, and age group is fever. The study also revealed AEFIs may have contributed to the death of 3 (0.000056%) per 5.3 million recipients. However, a causality assessment done by the Vaccine Safety Review Committee of independent experts showed no causality between the reported AEFI (deaths) and the YF vaccination. This indicates that the benefits of the vaccination outweigh the risk of adverse events or fatalities. Conclusion: In conclusion, it was found that the benefits of the Yellow Fever Vaccination (YFV 17D) outweigh the risk of adverse events or fatalities. Reported Adverse Events following the 2018 sub-national yellow fever vaccination per 5.3 million recipients were 459 representing 0.0086%. There was no causality between reported deaths 3 (0.000056%) and the YF immunization. The adverse events that follow yellow fever immunization are not strong and suggest that most of the respondents do not have serious repercussions after the vaccination. Therefore, YF vaccination has saved millions of people from potential vaccine-preventable deaths in Ghana and beyond its borders and did not cause more harm than health benefits.